ECMO Rescue Therapy in Diffuse Alveolar Haemorrhage: A Case Report with Review of Literature - Gautam Rawal (Journal of Clinical and Diagnostic Research, 2016)
Extracorporeal Membrane Oxygenation (ECMO) has evolved as a treatment option for patients having potentially reversible severe respiratory failure who are deteriorating on conventional ventilation. During ECMO, systemic anticoagulation is needed to maintain patency of the circuit. Therefore, ongoing haemorrhage remains a relative contra-indication to ECMO as it can further increase the bleeding. There is only limited evidence available for the use of ECMO in patients with alveolar haemorrhage. Most of these patients did not receive any anticoagulation during ECMO. We describe our experience with a patient who received intravenous anticoagulation during ECMO for refractory hypoxemic respiratory failure due to Diffuse Alveolar Haemorrhage (DAH) associated with Granulomatosis polyangitis (Wegner’s GPA). ECMO sustained life by maintaining gas exchange support and provided the time for the immunotherapy to be effective. We report the successful use of anticoagulation during ECMO in a patient with DAH.